Intraligamentous Hematoma of the Anterior Cruciate Ligament - Yasuaki Tamaki; Daisuke Hamada; Tadashi Mitsuhashi; Tokio Kasai; Takuya Mishiro; Takahiko Tsutsui; Kenichiro Kita; Koichi Sairyo (Case Reports in Orthopedics, 2019)
Lesions of the anterior cruciate ligament (ACL) are rare entities in clinical practice. Here, we present the case of an intraligamentous hematoma of the ACL. A 20-year-old man (height 173 cm, weight 62.9 kg, body mass index 21) with no significant past medical history developed progressively worsening pain and limitation of range of motion in the left knee due to minor trauma. No abnormality was found on plain radiography; however, magnetic resonance imaging revealed a cystic lesion in the intercondylar fossa that was hypointense on T1-weighted imaging and hyperintense on T2-weighted imaging. We performed knee arthroscopy, made a longitudinal incision in the anterior aspect of the ACL, and identified a hematoma. The patient’s postoperative course was uneventful. There is no evidence of recurrence at one year after surgery. Although the ACL is a relatively hypovascular structure, it does contain microscopic blood vessels. In this case, we speculate that the intraligamentous hematoma was the result of rupture of these very small blood vessels in response to a minor injury.